2015
DOI: 10.1001/jamaneurol.2015.0533
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Therapy With Interleukin 6 Receptor Blockade in Highly Active Neuromyelitis Optica Spectrum Disorder

Abstract: IMPORTANCE Neuromyelitis optica (NMO) is characterized by disabling relapses of optic neuritis and myelitis and the presence of aquaporin 4 antibodies (AQP4-abs). Interleukin 6, which is significantly elevated in serum and cerebrospinal fluid of patients with NMO, induces AQP4-ab production by plasmablasts and represents a novel therapeutic target.OBJECTIVE To evaluate the long-term safety and efficacy of tocilizumab, a humanized antibody targeting the interleukin 6 receptor, in NMO and NMO spectrum disorder. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
132
2
10

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 207 publications
(148 citation statements)
references
References 40 publications
4
132
2
10
Order By: Relevance
“…Owing to the crucial role of IL-6 in stimulating both B and T cells in autoimmune processes [13][14][15], tocilizumab was established as efficient in various autoimmune diseases, including rheumatoid arthritis and systemic lupus erythematosus [16][17][18]. Among the autoimmune central nervous system (CNS) disorders, a recent study reported a powerful disease modulation by tocilizumab in rituximab-refractory neuromyelitis optica (NMO) [19][20][21]. Regarding AE, successful treatment of contactin-associated protein-like 2 syndrome by tocilizumab was reported [22], and some experts suggested broader use of tocilizumab in antibody-medicated encephalitis [23].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Owing to the crucial role of IL-6 in stimulating both B and T cells in autoimmune processes [13][14][15], tocilizumab was established as efficient in various autoimmune diseases, including rheumatoid arthritis and systemic lupus erythematosus [16][17][18]. Among the autoimmune central nervous system (CNS) disorders, a recent study reported a powerful disease modulation by tocilizumab in rituximab-refractory neuromyelitis optica (NMO) [19][20][21]. Regarding AE, successful treatment of contactin-associated protein-like 2 syndrome by tocilizumab was reported [22], and some experts suggested broader use of tocilizumab in antibody-medicated encephalitis [23].…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The efficacy of tocilizumab is supported by the congruent results of 2 recent open-label studies reporting a total of 15 patients from Germany and Japan with AQP-IgG-positive NMOSD [121,122]. Araki et al [121] treated 6 females and 1 male with high disease activity (mean ARR 2.9±1.1, mean EDSS 5.1±1.7) monthly with 8 mg/kg tocilizumab as add-on therapy to either prednisolone, AZA, ciclosporin, or tacrolimus.…”
Section: Il-6 Receptor Inhibitionmentioning
confidence: 81%
“…Theoretically, the absence of attack-related inflammation could also release repair processes such as remyelination. Indeed, several studies investigating broad or selective immunosuppression reported an improvement of disability during the course of treatment [21,81,83,84,87,92,102,121,122].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations